Comparing short versions of the Alcohol Use Disorders Identification Test (AUDIT) in a military cohort. Issue 5 (October 2019) - Watterson, Jason; Gabbe, B; Dietze, P; Bowring, A; Rosenfeld, J V
Abstract : Background: The Alcohol Use Disorders Identification Test (AUDIT) is widely used for monitoring harmful alcohol consumption among high-risk populations. A number of short versions of AUDIT have been developed for use in time-constrained settings. In military populations, a range of AUDIT variations have been used, but the optimal combination of AUDIT items has not been determined. Methods: A total of 952 participants (80% male), recruited as part of a wider study, completed the AUDIT-10. We systematically assessed all possible combinations of three or four AUDIT items and established AUDIT variations using the following statistics: Cronbach's alpha (internal consistency), variance explained (R 2 ) and Pearson's correlation coefficient (concurrent validity). Results: Median AUDIT-10 score was 7 for males and 6 for females, and 380 (40%) participants were classified as having a score indicative of harmful or hazardous alcohol use (≥8) according to WHO classifications. A novel four-item AUDIT variation (3, 4, 8 and 9) performed consistently higher than established variations across statistical measures; it explained 85% of variance in AUDIT-10, had a Pearson's correlation of 0.92 and Cronbach's alpha was 0.63. The FAST, an established shortened AUDIT variant, together with several other four-item novel variants of AUDIT-10 performed similarly. The AUDIT-C performed consistently low on all measures, but with a satisfactory level of internal consistency (75%). Conclusion: Shortened AUDIT variations may be suitable alternatives to the full AUDIT for screening hazardous alcohol consumption in military populations. Four-item AUDIT variations focused on short-term risky drinking and its consequences performed better than three item versions. Trial registration number: ACTRN12614001332617.